P1 Diagnosis and stroke risk of atrial fibrillation in patients with atrial septal defects: A single centre experience. (2nd March 2016) - Abiodun, Aderonke; Moore, Heather; Bowater, Sarah; Thorne, Sara; Clift, Paul; Hudsmith, Lucy; Bono, Joseph De
Abstract : Background: Atrial fibrillation (AF) is one of the most common sustained tachyarrhythmias. It increases risk of developing stroke by up to five times. There is an increased incidence in patients with adult congenital heart disease (ACHD). The CHA2 DS2 VASC scoring system is validated for assessing the risk of ischaemic stroke in AF in the general population. Its role in ACHD is unclear. This study assesses the burden of AF in patients with uncomplicated atrial septal defects (ASD). Methods: A retrospective analysis of the ACHD database of all patients at a large quaternary specialist ACHD centre. Results: 135 (3%) patients with a diagnosis of ASD and co-existing AF were identified out of 4500 patients under regular follow up at Queen Elizabeth Hospital Birmingham. 101 (75%) secundum ASD, 12 (9%) sinus venosus ASD, 1 (1%) coronary sinus ASD and 21 (15%) unclear. 47 (35%) surgical closures, 28 (21%) percutaneous closure, 57 (42%) unrepaired, 3 (2%) both surgical and percutaneous. There were 7 residual defects post closure. -The mean age was 67.8(+/-12.8) years, range 36–90 years, 65 male (48.1%). -The mean CHA2 DS2 VASC score was 2.21 (Range 0–6). -The mean age of onset of AF was 56(+/-12.3) years. In 40% the AF was asymptomatic. -90% of patients with a CHA2 DS2 VASC score of 2 or more were anticoagulated with either warfarin or a novel oral anticoagulant (n = 75). 11 patients had suffered a stroke (8.15%). -7 presented initially with a stroke and asymptomatic AF; of these 6 were also found to have ASDs after the stroke. The mean age stroke occurred was 58.7(+/-20) years. The mean CHA2 DS2 VASC score for patients who had a stroke was 4.18 (Range 2–6). Discussion: The incidence of AF in ASDs is high and is frequently asymptomatic. AF and strokes occur at a young age in this population. A significant proportion of our patients presented for the first time with a stroke and asymptomatic AF. Expert consensus currently advocates screening for arrhythmias in certain ACHD groups but not ASD. This data suggest that patients with ASD should be actively screened for AF. The role of the CHA2 DS2 VASC score if unclear in these patients but a high CHA2 DS2 VASC does appear to correlate with a higher incidence of stroke.